2006
DOI: 10.1002/hipo.20164
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal cell proliferation is reduced following prenatal ethanol exposure but can be rescued with voluntary exercise

Abstract: The ingestion of ethanol during pregnancy has a number of deleterious consequences for the unborn offspring, producing structural and functional deficits that affect the brain and many other organs into adulthood. The hippocampus is a brain area that is particularly sensitive to ethanol's adverse effects. In a previous study we showed that voluntary exercise can ameliorate deficits in long-term potentiation and behavior that occur following prenatal ethanol exposure (Eur J Neurosci, 2005, 21, 1719-1726). In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
100
1
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(116 citation statements)
references
References 47 publications
8
100
1
5
Order By: Relevance
“…The direction and magnitude of changes in neurogenesis in models of foetal alcohol spectrum disorders depend on several factors, including blood alcohol concentration attained, frequency of exposure and phase of gestation during which alcohol is administered [40]. In agreement with our findings, some studies have reported no significant changes on proliferation and survival of neuronal precursors following exposure to alcohol throughout the pregnancy [41,42], but others have after similarly long exposure [17]. Further, a study in females revealed no effects of prenatal alcohol exposure on hippocampal cytogenesis and survival [43].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The direction and magnitude of changes in neurogenesis in models of foetal alcohol spectrum disorders depend on several factors, including blood alcohol concentration attained, frequency of exposure and phase of gestation during which alcohol is administered [40]. In agreement with our findings, some studies have reported no significant changes on proliferation and survival of neuronal precursors following exposure to alcohol throughout the pregnancy [41,42], but others have after similarly long exposure [17]. Further, a study in females revealed no effects of prenatal alcohol exposure on hippocampal cytogenesis and survival [43].…”
Section: Discussionsupporting
confidence: 81%
“…Similarly, recent research has shown that exposure to either of these drugs during prolonged periods of embryonic development can have long-term effects on adult neurogenesis [16,17], raising the possibility that such alterations may underlie long-lasting deficits in learning and memory function. However, the effects of embryonic exposure to MDMA and alcohol combined have not been previously investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, exercise during pregnancy can up-regulate postnatal neurogenesis in the offspring at P9 (41). Voluntary exercise is also able to compensate for decreased levels of proliferation induced by prenatal ethanol exposure (42). In addition, an enriched environment is effective in boosting neuronal numbers and enhancing cognitive function after status epilepticus in P20 mice (43).…”
Section: Discussionmentioning
confidence: 99%
“…(Redila et al, 2006). Pregnant female mice were injected with BrdU once, and animals were allowed to survive for either 2 or 96 h. Embryonic brains obtained from either E14 or E18 mice were sectioned and mounted on coverslips, and DNA was denatured by incubating the slides in HCl for 30 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%